The Requirement for Information Governance Policy Framework in Malaysian Public Sector - Abdul Halim, Noursilawati; M.Yusof, Zawiyah; Azan M. Zin, Nor (International Journal of Engineering and Technology, 2018)
The Information Governance (IG) Policy Framework sets out the standard to be applied for managing information including the principle, standard, procedure and guideline. This study seeks to identify the significant and appropriate factors underlying the IG policy in common. The identified factors are then verified for their appropriateness to be practiced in the public sector in Malaysia. The literature suggests that control, quality, compliance, transparency, value, accessibility, security, sharing, accountability, and privacy are the core factors essential for the IG policy framework. A survey method, using qualitative approach with interview, observation, and document content analysis are used as the data collection techniques. The sample is determined by purposive sampling and snowball and the Malaysian Administrative Modernisation and Management Planning Unit (MAMPU) was chosen as a case study. Findings show that there is as yet no appropriate IG policy framework which can be referred to by the public sector in executing information governance initiative. The proposed framework is of help especially to MAMPU in getting a guide for the execution the IG initiative in the Malaysian public sector. Â Â Â Â